Retolació ceràmica urbana dels segles XVIII i XIX: les fàbriques de València. - BUENAVENTURA, BEATRIU NAVARRO I.; I. MOLINA, JOSEP LLUÍS CEBRIÁN (Scripta, 2020)
The cities began to signal the names of streets and public buildings with tiles, and to number the houses, in accordance with the Royal Decree of 1769 promulgated by Carles III. In this paper we study the evolution of urban signage throughout the 18th and 19th centuries. Based on documented examples -Xàtiva, Sogorb, Valencia, Ciutat de Mallorca- and the preserved ceramic tiles and plates, we analyze this aspect of Valencian tilework.